The Role of Psychological Suggestion Combined With Sports in Music Teaching - Liusong Yang; Hui Du (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
To alleviate the psychological burden on students and facilitate the efficient delivery of high-quality teaching information, psychological suggestions can be employed. Psychological suggestion involves subtly influencing the subconscious mind through discussions, expressions, gestures, attire, environmental factors, and a non-confrontational, non-critical, and non-resistant approach. This approach aims to stimulate students' internal psychological needs and potential indirectly, resulting in meaningful changes in their psychological states. In the context of music teaching, utilizing suggestion techniques is valuable for altering students' intrinsic motivations and psychological potential. By reducing the psychological stress students may experience in the classroom, it becomes possible to achieve high-speed, high-quality transmission of educational content. This approach represents a significant strategy for attaining educational objectives. Music classroom instruction, aside from imparting subject knowledge and honing essential skills, places greater emphasis on fostering students' enthusiasm for learning and their ability for self-directed learning. In this experimental study, a total of 100 students participated, including 72 male and 28 female students. The participants were drawn from various academic backgrounds, including four classes of music education majors in the Music Department, 18 students (13 males and 5 females) from the 22nd-grade Music Information Technology Department, 27 students (15 males and 12 females) from the 22nd-grade Music Leisure Major in the Music Economic Management College, and 19 students (9 males and 10 females) from the 22nd-grade Human System Applied Psychology Major. This research utilized teaching experiments, questionnaire surveys, and logical analysis, focusing on students from a music conservatory. The study conducted a comparative experimental investigation involving a Psychological Suggestion Experimental Group and a Normal Teaching Control Group. The TOPS questionnaire was administered during the teaching sessions of the experimental group. Students were asked to complete the questionnaire honestly and anonymously. In the experimental group, which consisted of four classes, there were 28 students in Group 3 (all of whom were male), and 28 students in Group 13 (comprising 6 males and 22 females). Additionally, there were 27 students (15 males and 12 females) majoring in Music Leisure in the School of Music Economics and Management at Grade 22, as well as 19 students (9 males and 10 females) majoring in Applied Psychology in Grade 07. The TOPS scale was distributed to both the experimental and control groups. The average and standard deviation of the eight factors of the TOPS training strategy for male and female amateur students were calculated. Among male students, the highest average score was observed in the "Emotional Control" factor, with a mean score of 3.54. For female students, the "Automation" factor had the highest average score, at 3.34. Conclusion: Integrating psychological suggestion into music education can effectively enhance student engagement and enthusiasm in the classroom. This approach enables students to better connect with their instructors and actively participate in their learning. When compared to traditional music teaching methods, the judicious use of psychological cues aids students in the experimental group in successfully accomplishing their learning objectives. Moreover, this approach assists novice students in developing a habit of actively engaging with music, which contributes to the cultivation of a lifelong appreciation for music.